2012
DOI: 10.1539/joh.11-0063-fs
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Sexual Harassment in Two General Hospitals in Taiwan: The Incidence, Perception, and Gender Differences

Abstract: Workplace Sexual Harassment in Two General Hospitals in Taiwan: The Incidence, Perception, and Gender Differences: Liang‐Jen WANG, et al. Department of Psychiatry, Chang Gung Memorial Hospital at Keelung, Taiwan— Objectives The aims of this study were to examine sexual harassment (SH) among hospital staffs in Taiwan, in terms of three‐month incidence rate, the frequency of each type and the perception of SH, perpetrated by coworkers, patients and patients' families and to investigate the gender differences for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 27 publications
1
15
1
Order By: Relevance
“…Sexual harassment: prevalence, types and consequences Sexual harassment has been defined as any "unwanted or unwelcome conduct of a sexual nature, in a workplace or in connection with work, which makes a protected person feel humiliated, intimidated, discriminated against or offended" (International Labour Organization, 2001) and is relatively frequent in health care settings (e.g. Çelik and Çelik, 2007;Somani et al, 2015;Wang, 2012). Although the estimated prevalence varies according to country, research methodology, and specific work setting, it has been estimated that one in four nurses are exposed to sexual harassment (Spector et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Sexual harassment: prevalence, types and consequences Sexual harassment has been defined as any "unwanted or unwelcome conduct of a sexual nature, in a workplace or in connection with work, which makes a protected person feel humiliated, intimidated, discriminated against or offended" (International Labour Organization, 2001) and is relatively frequent in health care settings (e.g. Çelik and Çelik, 2007;Somani et al, 2015;Wang, 2012). Although the estimated prevalence varies according to country, research methodology, and specific work setting, it has been estimated that one in four nurses are exposed to sexual harassment (Spector et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This study's literature search turned up substantial evidence of sexual harassment of health workers especially female nurses, although the link to corruption in employment or promotion was implicit and not explicit [47][48][49][50][51][52][53][54]. A 2014 quantitative review of studies on sexual harassment of nurses turned up a total of 136 articles with data on 151,347 nurses from 160 samples and revealed that up to 25% of nurses have experienced sexual harassment at work [55].…”
Section: Sextortionmentioning
confidence: 99%
“…Sensitive issues change from one culture to another so you might need to be judicious in choosing the questions you might ask a particular cultural group. For example, studying the issue of "sexual harassment" among workers (29) or students (30) could be categorized as a very sensitive issue. Sensitive issues might be asked later in the questionnaire by explaining why these personal questions are important to be asked.…”
Section: Never Begin Your Questionnaire With Sensitive Questionsmentioning
confidence: 99%